(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
This essay aims at exploring the possibility to apply a phenomenological approach to the relation between religions and bioconstitutionalism. The author focuses on the legal framework of such an approach, that is an intercultural conception of “laicità”, understood as procedural cognitive process to be realized by balancing legal claims, rights and existential conceptions of religious actors. Conclusions are dedicated to the definition of an interdisciplinary paradigm of legal subjectivity which may combine the traditional, humanistic and constitutional perspective to the evolutionist-anthropological one resulting from the most recent evidence of cognitive sciences of religion (CSR).